Effect of Sub Maximal Dynamic and Static Exercises on QTc interval in Healthy Young Men - Bharti Bhandari; Lokesh Kumar; Anjum Datta; Sabyasachi Sircar (Journal of Clinical and Diagnostic Research, 2015)
Introduction: The QTc interval depends largely on cardiac repolarization since the duration of cardiac depolarization is fairly constant in the normal heart. QTc at rest as well as during exercise has many clinical implications. In this study, we have compared the relative effects of dynamic and static exercise on QTc. Aim: To measure QTc interval in young men at rest and also assess how it is further modulated by submaximal dynamic and static exercises. Materials and Methods: This observational study was conducted in the Department of Physiology on 30 non-obese young men randomly selected from the students of our institute after obtaining the consent and institutional ethical clearance. Continuous blood pressure monitoring and ECG recording was done in the subjects. Baseline (pre-exercise), post submaximal dynamic (Harvard’s step test) and post submaximal static exercise (hand-grip exercise) recordings of ABP and ECG were taken for analysis. The measured QT interval was corrected for heart rate using the formula of Bazett et al., {QTc=QT/RR1/2}.Statistical analysis was done using Graph pad Prism 5 software (California, USA). The baseline and postexercise data were compared using paired t-test. A p<0.05 was taken to be statistical significant. Results: There were statistically significant increases in HR, SBP, DBP and QTc interval after dynamic exercise in comparison to the baseline values (p<0.05). Significant increase in HR (p<0.05) with no significant change in QTc and other cardiovascular parameters were recorded following static exercise (p>0.05). Conclusion: Significant increase in QTc interval was observed after dynamic exercise, however, no change in QTc was observed following static exercise, and hence we conclude that static exercises may not be useful in assessing the cardiovascular status of an individual or in predicting cardiovascular events.